The Impact of Duolingo on Vocabulary Acquisition among English Department Students at Al-Jufra University - Masoudah Zaydan Ali ALnalouti (Journal of Libyan Academy Bani Walid, 2025)
This study examines the influence of Duolingo on vocabulary learning in Libyan EFL students at the English Department of Al-Jufra University. In the contemporary educational scene, technology-enhanced tools like social media and mobile applications have become indispensable in Facilitating language acquisition. Duolingo, a prominent educational application, is engineered to enhance vocabulary acquisition through interactive, gamified courses. The research utilized a descriptive quantitative methodology, employing a structured questionnaire with 15 items to collect data from a purposive sample of 30 students. The results demonstrate that most participants regard Duolingo as an efficient and stimulating resource for acquiring and retaining new language. Participants indicated regular exposure to novel vocabulary, enhanced comprehension via visual aids, and facilitated memorization due to the app's design. The findings also underscore students' inclination to use such tools into formal educational settings. The study advocates for the integration of Duolingo and analogous applications within the academic curriculum to improve EFL students' vocabulary proficiency and motivation.